Agile Governance Public Information Management at the Communication, Informatics, and Statistics Service of Riau Province - Hermansyah Hermansyah; Harapan Tua; Mayarni Mayarni (CV. Publikasi Indonesia, 2024)
This study aims to analyze the implementation of agile governance in public information management at the Riau Province Communication, Informatics and Statistics Service (Diskominfotik). Agile governance is a governance approach that emphasizes flexibility, responsiveness, and rapid collaboration in providing public services. The research method used is qualitative descriptive with an explanatory approach. Data collection was carried out through observation, interviews, and document studies analyzed using Nvivo 14 software. The results of the study indicate that the implementation of agile governance at Diskominfotik Riau is still faced with a number of obstacles, including limited knowledge and capacity of human resources (HR) in understanding the concept and a bureaucratic structure that does not fully support flexibility. In addition, performance evaluations that are not yet based on quick wins slow down the adaptation process. Nevertheless, Diskominfotik Riau has utilized various digital platforms to provide access to public information, although improvements need to be made in terms of responsiveness and timeliness of service. Recommendations from this study include increasing training for HR, implementing a more flexible governance model, and periodic evaluations based on short-term results. The implementation of agile governance is expected to improve the quality of public services and strengthen public trust in government transparency.